2005
DOI: 10.1136/bmj.38705.470590.55
|View full text |Cite
|
Sign up to set email alerts
|

Didgeridoo playing as alternative treatment for obstructive sleep apnoea syndrome: randomised controlled trial

Abstract: Objective To assess the effects of didgeridoo playing on daytime sleepiness and other outcomes related to sleep by reducing collapsibility of the upper airways in patients with moderate obstructive sleep apnoea syndrome and snoring. Design Randomised controlled trial. Setting Private practice of a didgeridoo instructor and a single centre for sleep medicine. Participants 25 patients aged > 18 years with an apnoea-hypopnoea index between 15 and 30 and who complained about snoring. Interventions Didgeridoo lesso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
161
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(168 citation statements)
references
References 19 publications
(19 reference statements)
3
161
1
3
Order By: Relevance
“…Perhaps if exercise produced strengthening of the pharyngeal musculature, upper airway collapsibility would be diminished, and SDB would be less. One recent clinical trial using a unique wind instrument to treat SDB suggests this may occur [32]. Alternatively, physical training may lead to redistribution of adipose tissue away from the upper airway.…”
Section: Discussionmentioning
confidence: 95%
“…Perhaps if exercise produced strengthening of the pharyngeal musculature, upper airway collapsibility would be diminished, and SDB would be less. One recent clinical trial using a unique wind instrument to treat SDB suggests this may occur [32]. Alternatively, physical training may lead to redistribution of adipose tissue away from the upper airway.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to touch in communication, touch can also be employed in psychotherapy (Phelan 2009) and nursing (Gleeson and Timmins 2005). Examples range from basic comforting touches and massaging to alternative therapies such as acu-pressure, Reiki, vibroacoustic therapy, and low-frequency vibration (Wigram 1996;Kvam 1997;Patrick 1999;Puhan et al 2006;Prisby et al 2008). See Dijk et al (2013) for more examples on mental, healthrelated, and bodily effects of touch.…”
Section: Touch In Social Communicationmentioning
confidence: 99%
“…However, the overall level of such symptoms was very low. In the studies by Puhan [29] and Guimaraes [30], no adverse or unexpected events were mentioned in relation to either group. Intention-to-treat analysis There were no dropouts from the didgeridoo study [29] and this was the only study in which an intention-to-treat analysis was reported.…”
Section: Adverse Eventsmentioning
confidence: 92%
“…We found three types of intervention aimed at increasing muscle tonus: (1) intraoral electrical neurostimulation [28], (2) didgeridoo playing [29], and (3) oropharyngeal exercises [30].…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation